Weaving public policies and innovation ecosystems: Integrative insights for sustainable development and strategic collaboration - Koch, L. L.; Tonial, G.; Matos, F.; Pletsch, A. L. B. (European Journal of Innovation Management, 2026)
Purpose This research examines the literature on public policies and innovation ecosystems, proposing a research agenda. Public policies and the development of innovation ecosystems are strategies to promote economic development and achieve the Sustainable Development Goals. Design/methodology/approach Using an integrative systematic review by the PRISMA-P protocol, data were collected from the Scopus and Web of Science databases. Initially, 119 documents were identified, and after applying inclusion and exclusion criteria, 51 articles were analysed. The main discussions were represented in analytical categories generated by artificial intelligence codes from the ATLAS.ti24 software, organised in a strategic diagram with four themes: specialised themes, driving themes, basic themes and emerging themes. Findings Regarding the four identified thematic categories, the following results were obtained: Specialised themes: Open innovation and public policies, showing how public policies can create environments conducive to innovation; Driving themes: Sustainability and digital platforms and innovation, fundamental for the circular economy and sustainable business models; Basic/Transversal themes: Partnerships and collaboration, highlighting the importance of mentoring networks and institutional support and Emerging themes: Circular economy, with significant opportunities for future research, especially in integrating education, entrepreneurship and sustainability. Originality/value The study details how different dimensions of public policies impact the effectiveness and resilience of innovation ecosystems in various geographical contexts. It proposes a practical and theoretical research agenda, suggesting adaptive policies to improve stakeholder dialogue and reinforce intersectoral collaboration. Recommendations include strengthening public funding policies for startups, promoting open innovation and encouraging digital platforms to facilitate interaction between governments, businesses and civil society.